New Algebraic Method for Solving the Axial N - Index Transportation Problem Based on the Kronecker Product (MATEMATIKA, 2005)
A new algebraic method to solve the axial two and three - index transportation problem that is based on the Kronecker product of matrices is suggested. It is applied to solve the axial N(N > 2) - index transportation problem, as a general case. Further, the optimal feasible solution of these problem is obtained. The proposed method is considered algebraic, simple, robust and easily programmable. Keywords: Transportation problem; Kronecker product; partitioned matrix.